Examining the Benefits of Water Births in a Hospital Setting: Perspectives from Midwives and Nurses - Ghalib Qadous, Shurouq; Firdaus, Mohd Khairul Zul Hasymi (Jurnal Perilaku Kesehatan Terpadu, 2023)
Objective: This study aimed to investigate the impact of midwifery-led care on maternal outcomes, maternal satisfaction, and newborn health in a hospital setting. Specifically, the study sought to compare the effects of midwifery-led care to standard care models, assess maternal preparedness for childbirth, explore rates of medical interventions, evaluate maternal satisfaction, and examine newborn health outcomes. Methods: A total of 200 expectant mothers receiving prenatal care at a tertiary hospital were recruited and randomly assigned to two groups: Group A (midwifery-led care) and Group B (standard care). Participants' demographic information, medical history, and preferences related to prenatal care were collected using a structured questionnaire. Validated surveys, including the Edinburgh Postnatal Depression Scale (EPDS), were used to assess postpartum depression. Medical records and prenatal visits were reviewed throughout the pregnancy, and postpartum follow-ups were scheduled to assess maternal outcomes. Statistical analyses were performed to compare outcomes between the two groups. Results: Participants in the midwifery-led care group reported significantly higher levels of birth preparedness (p < 0.001), and rates of medical interventions during childbirth, including cesarean sections, were significantly lower compared to the standard care group (p < 0.05). Maternal satisfaction scores were significantly higher in the midwifery-led care group (p < 0.001). Additionally, the midwifery-led care group showed lower rates of postpartum depression (p < 0.01) and higher rates of exclusive breastfeeding at six weeks postpartum (p < 0.05). Neonates born to mothers in the midwifery-led care group had significantly lower rates of neonatal complications (p < 0.01). Conclusion: The findings of this study provide strong evidence for the positive impact of midwifery-led care on maternal outcomes, maternal satisfaction, and newborn health. The personalized and woman-centered approach of midwifery-led care contributes to improved maternal preparedness, reduced medical interventions, increased maternal satisfaction, lower rates of postpartum depression, and better newborn health outcomes. These results highlight the potential benefits of integrating midwifery-led care models into maternity services, aiming to enhance the overall birthing experience and improve maternal and infant health outcomes.